Marginal fit and retention force of zirconia resin-bonded fixed dental prostheses in the posterior region with different designs - Yue Yin; Kosuke Nozaki; Reina Nemoto; Omnia Saleh; Yayoi Oishi; Mayuko Matsumura; Wataru Komada; Hiroyuki Miura; Kenji Fueki (Elsevier, 2024)
Background/purpose: Retainer debonding of resin-bonded fixed dental prostheses (RBFDPs) is one of the major reasons for their lower survival rates than fixed dental prostheses (FDPs) with full-coverage crowns. Recent advances in milling technology have enabled the fabrication of RBFDPs with complex retainers (D-shaped designs). This study aimed to assess the marginal fit and retention force of zirconia RBFDPs with inlay-, L-, and D-shaped designs to clarify their clinical applications. Materials and methods: Three abutment teeth models without maxillary second premolars were created using inlay-, L-, and D-shaped retainer designs. The zirconia RBFDPs were designed and fabricated according to the manufacturer's instructions (n = 10). The marginal gap was measured using the silicone replica technique. Zirconia frameworks were bonded to the abutment teeth using resin cement. Tensile test was conducted after thermal cycling and dynamic loading tests. The loads during debonding or fracture were recorded. The failure pattern was analyzed by observing the fracture surface using a scanning electron microscope. Results: D-shaped RBFDPs showed a significantly larger marginal gap than inlay- and L-shaped RBFDPs (P < 0.05). However, the mean marginal values were clinically acceptable (<120 μm). The D-shaped model exhibited the highest tensile strength in the tensile tests. The inlay-shaped and most of the D-shaped RBFDPs experienced debonding with cohesive failure, whereas the L-shaped RBFDPs showed fractures near the connector. Conclusion: The D-shaped retainer design was superior to the inlay- and L-shaped designs with respect to the inhibition of retainer debonding. However, the marginal fitness needs to be improved.